On the Potential Interaction Between Labour Market Institutions and Immigration Policies - Claudia Cigagna; Giovanni Sulis (Institute for the Study of Labor (IZA), 2015)
Using data on migration flows for a sample of 15 OECD countries over the period 1980-2006, we analyse the effect of unemployment and labour institutions such as employment protection legislation, coverage of unemployment benefits, minimum wages, union power and tax wedge on migration flows. We allow for interactions of these institutions with migration entry laws, as both affect equilibrium wages and employment in destination countries, influencing mobility decisions of immigrants. We find strong and negative effects of unemployment, employment protection and migration policy on flows. The negative effect of migration policy on flows is larger in countries with high than in countries with low employment protection. We find positive effects for minimum wages, unemployment benefits and union power. We deal with potential endogeneity of the variables of interest and report heterogeneous effects depending on the group of countries of origin and destination.
Keywords: J61; J50; F22; 330; international migration flows; labour market institutions; migration policies